“Clogging layer” at regulated river beds - implications for river-groundwater exchange - Siergieiev, Dmytro; Lundberg, Angela; Widerlund, Anders; Öhlander, Björn (Luleå tekniska universitet, Geovetenskap och miljöteknik, 2013)
Within the EU-project GENESIS (2013), aiming to provide scientific basis and technical guidance for the update of the EU Groundwater Directive, Luleå University of Technology is investigating possible effects of hydropower regulation on surface water (SW)- groundwater (GW) exchange. The study compares SW, GW and hyporheic processes for the unregulated Kalix River and the regulated Lule River. Hydropower has long been regarded a fairly green energy source but today negative effects have become obvious (Renöfält et al. 2010).The hyporheic zone (HZ) accommodates most of the SW-GW exchange of solutes just beneath and along a river, dampens heat fluxes, processes pollutants and is essential for ecosystems.The study observes SW and GW (in wells orthogonal to the river) at one site in each river. In these, hydrological (water level, hydraulic conductivity, tracer test) and geochemical (temperature, electrical conductivity, water/soil chemistry) measurements were performed during several seasons.The presence of natural high-flow events in the Kalix River removes fines from the river bed, maintaining good SW-GW connectivity that favours hyporheic exchange (Brunke and Gonser 1997). Altered discharge of the regulated river (reduced flow peaks and velocity, daily discharge fluctuations) facilitated deposition of fine sediments at the river bed forming a “clogging layer” (Blaschke et al. 2003). The bed in the regulated river has two orders of magnitude lower hydraulic conductivity than that at the unregulated site and restricts the SW-GW exchange.Reduced hydraulic connectivity between SW and GW at the regulated Lule River site suggests decreased fluxes across the river-aquifer interface (Siergieiev et al. 2013), and thus reduced size of the HZ which is not always the case in regulated rivers (Sawyer et al. 2009).Decreased hyporheic velocities led to increased residence time and favored prolonged contact between water and soil matrix that stimulated biogeochemical transformations. As a result, the electrical conductivity of ...